Clinical Presentation, Complications and Early Predictors for Poor Outcomes in Pediatric Myocarditis in a Tertiary Care Hospital - Khalid, Adeel; Kamraan, Amber; Rafiq, Nida; Kumari, Veena; Sheikh, Abdul Sattar; Patel, Najma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate common clinical presentation, complications and poor prognostic outcomes in children with acute myocarditis. Study Design: Prospective longitudinal study. Place and Duration of Study: Pediatric Cardiology Department, National Institute of Cardiovascular Disease Karachi Pakistan, from Feb to Aug 2020. Methodology: The children aged one month to 16 years were included in the study. Clinical, demographic features, Electrocardiogram, Echocardiography, management, complications, and immediate outcomes were recorded. Results: The total number of patients enrolled was 161. The median age was 5.01 ± 3.38 years for 66.4% of males and 33.5% females, mean Duration of symptoms was 8.35 ± 3.49 days. Upper respiratory tract infection was present in 84 (52.2%) and diarrhea in 8 (5%) in the preceding illness. Symptoms and signs include loss of appetite in 153 (96.27%), irritability in 148 (91.9%), vomiting in 132 (82%) and abdominal pain in 112 (69.6%), tachycardia in 148 (91.9%) and pallor in 143 (88.8%). Low voltage ECG was present in 125 (77.6%), arrhythmias in 12 (7.45%) and heart block in 6 (3.7%). Left ventricle end-diastolic dimensions (LVIDD)>4SD were present in 30.2% and LV end-systolic dimensions (LVIDS)>4SD in 19.5%, Left ventricular ejection fraction (LVEF)mean was 21.13 ± 5.07 vs 23.45 ± 3.31 at discharge. 9.21% of patients expired, out of which 78.5% had Left bundle branch block (LBBB), mean LVEF was 16.24 ± 3.16, LVID d>4SD in 78%, and LVIDs>4SD in 30%. Conclusion: The most frequent presentations were loss of appetite, difficulty breathing, irritability and abdominal pain. Tachycardia and pallor were......